A gap and damage in the security of payment cards - Sūdžius, Vytautas; Mackevičius, Vytautas (Business: Theory and Practice, 2006)
In the article the payment card problems are connected with a gap and damage in the security system. The main purpose of the article is to evaluate security level of the payment card system and find its security gap and damage. Tasks of the article are as follows: to evaluate the damage level of the payment card system for the card system members, to measure the payment card security features, security of the work organization and systems, to examine and evaluate the merits and demerits of security models used in European Banks, to propose the solution how to minimize the damage in payment card system. The Method of research: analysis of nonfiction, continuous census of fraud cases, information analysis using statistical methods, comparative analysis, experts opinion, analysis of material of case investigation and reports, analysis according to the dominating fraud types and indicators, document process analysis. The article’s research shows the weakness of physical card security features, nonsecure customer financial – credit possibility and card parameters management, outworn equipment and methods of system analysis and monitoring, the lack of co-operation between the members of the payment card system. The big part of indicated demerits could be covered by migrating to the new card system and equipment. In addition, it was proposed to create the co-operation schemes between system members and third party service providers, to set the loyalty programme for the merchants and police, to introduce more secure authorisation system modules. Article in Lithuanian. Atsiskaitymų mokėjimo kortelėmis saugumo spragos ir patirti nuostoliai Santrauka. Atsiskaitymų mokėjimo kortelėmis saugumas – aktuali problema visame pasaulyje, ne išimtis ir Lietuva. Straipsnyje nagrinėjama atsiskaitymų mokėjimo kortelėmis sistema įvairiose Europos valstybėse, neskaidant jos į bankų grupes. Tyrimo rezultatai apibūdina esminius atsiskaitymų mokėjimo kortelėmis sistemos saugumo trūkumus Europos ir pasauliniu mastu. Pagrindinėmis nusikaltimų su kortelėmis problemomis Europoje išlieka kortelių klastotės (34 proc. visų nusikaltimų), pamesta ar pavogta kortelė (28 proc. visų nusikaltimų) ir niekada negauta kortelė (27 proc. visų nusikaltimų su kortelėmis). Reikšminiai žodžiai: pažeidžiamumo lygis, saugumo spragos, nusikaltimų su kortelėmis rodikliai, statistika, kortelių klastotės.